ChemInform Abstract: Remote C—H Activation of Quinolines Through Copper‐Catalyzed Radical Cross‐Coupling. Issue 30 (July 2016) - Xu, Jun; Shen, Chao; Zhu, Xiaolei; Zhang, Pengfei; Ajitha, Manjaly J.; Huang, Kuo‐Wei; An, Zhongfu; Liu, Xiaogang
Abstract: Various N‐aryloyl or N‐alkyl protected 8‐aminoquinolines are efficiently sulfonylated in position 5 using a broad range of aryl or hetaryl sulfonyl chlorides.